A fast and simple assay to quantify bacterial leukotoxin activity - Oppermann, Tobias; Schwarz, Stefan; Busse, Nadine; Czermak, Peter (My University, 2016)
Background: Mannheimia haemolytica is the primary bacterial pathogen in causing bovine respiratory disease with tremendous annual losses in the cattle industry. The leukotoxin from M. haemolytica is the predominant virulence factor. Several leukotoxin activity assays are available but not standardized regarding sample preparation and cell line. Furthermore, these assays suffer from a high standard error, a prolonged time consumption and often complex sample pretreatments, which is important from the bioprocess engineering point of view. Results: Within this study, an activity assay based on the continuous cell line BL3.1 combined with a commercial available adenosine triphosphate viability assay kit was established. The leukotoxin activity was found to be strongly dependent on the sample preparation. Furthermore, the interfering effect of lipopolysaccharides in the sample could be successfully suppressed by adding polymyxin B. We reached a maximum relative P95 value of 14%, which is more than seven times lower compared to current available assays as well as a time reduction up to 88%. Conclusion: Ultimately, the established leukotoxin activity assay is simple, fast and has a high reproducibility. Critical parameters regarding the sample preparation were characterized and optimized making complex sample purification superfluous.
Citation: Oppermann T, S Schwarz, N Busse, P Czermak: A fast and simple assay to quantify bacterial leukotoxin activity, Electronic Journal of Biotechnology, (2016). Vol. 24 http://dx.doi.org/10.1016/j.ejbt.2016.10.001
Keywords: ATP assay; Bacterial pathogen; Bovine respiratory disease; Cattle industry; Critical parameters; Lipopolysaccharides